STUDY OF SEDIMENTATION RATE AT SAMPEAN BARU RESERVOIR USING HEC-RAS 5.0.3 - Aviva, Yulia Nur (Kern : Jurnal Ilmiah Teknik Sipil, 2011)
Reservoir is a water building that serves to collect water during the rainy season and release the discharge in the dry season. Sampean Baru Reservoir is located in Bunotan Village, Tapen District, Bondowoso. Sampean Baru Reservoir is used for irrigation needs and as a micro power plant. In addition to having many functions of the condition and maintenance of the reservoir must be considered. One factor that can reduce the functioning of the reservoir is sediment. The process of sedimentation is the sedimentation of erosion that is carried by the flow of water in a place where the flow slows down. So the higher the level of soil erosion, the more sediments are brought. In this study calculate sedimentation rate at Sampean Baru reservoir using HEC-RAS 5.0.3 program the areas reviewed for upstream that is Maesan and downstream that is on the Sampean Baru reservoir which has a length of 44.44 km. Sediment volume in 2004 amounted to 858,236.9195 m3. The calculation result using HEC-RAS program obtained sediment volume of 2.473.049 ton / th = 1.466.905 m3. So it can be seen from 2004 to Â 2017 there was an increase in sediment volume by 70.92%.